Trauma-Sensitive Yoga: A Collective Case Study of Women's Trauma Recovery from Intimate Partner Violence. (2nd January 2019) - Ong, Isabelle; Cashwell, Craig S.; Downs, Holly A.
Abstract: More than 1 in 3 women in the United States experience intimate partner violence (IPV) and many of them develop post-traumatic stress disorder (PTSD). Trauma-sensitive yoga (TSY), a structured, body-oriented yoga practice, has been reported for its potential to ameliorate PTSD symptoms. The purpose of the study was to examine adult female IPV survivors' experiences of recovery from IPV and trauma as facilitated by an 8-week TSY intervention using a collective case study research design. Participants ages 26 to 52 from diverse ethnic backgrounds participated in the study's 4 phases. Measures used include the Clinician-Administered PTSD Scale–5, Subjective Units of Distress Scale, pre- and post-interviews, and observations. Analyses reflected a moderate change in participants' PTSD scores attributed to the TSY intervention. Collective themes that emerged include physiological, emotional, and spiritual benefits. Although exploratory, the study illuminates the potential efficacy of TSY for facilitating multifaceted trauma recovery.